Polishing material, polishing pad and preparation method and application of polishing pad
By using a combination of fillers, surfactants, ether compounds and resins in the polishing material, the intermediate is formed and dispersed, the problem of insufficient physical and mechanical properties of the resin in the prior art is solved, and the preparation of high-performance polishing materials is realized, and the processing needs of higher precision semiconductor chips is met.
Patent Information
- Application Number
- CN202411271602.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing polishing pad preparation methods have insufficient physical and mechanical properties of resin, fewer active functional groups of additives or coarse particles, making it difficult to achieve the purpose of significantly improving the physical and mechanical strength of polyurethanes, and the wear resistance and adhesion properties have not yet reached the needs of semiconductor chip processing with higher precision.
An intermediate is formed by heating and stirring, and then dispersed in an organic solvent and stirred with the resin solution to form a polishing material. This method improves the wear resistance and mechanical properties of the polishing material through addition polymerization reaction of unsaturated double bonds and effective chimerization of fillers.
It achieves excellent wear resistance and mechanical properties of polished materials, meets the needs of higher precision semiconductor chip processing, and simplifies the preparation process, which is suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor chip polishing, and in particular relates to a high-performance polishing material, a polishing pad, and a preparation method and application thereof. Background Art
[0002] The semiconductor core contains a multi-layer microscopic circuit structure, which is mainly formed by forming grooves on the silicon wafer through photolithography and etching processes, and also requires the use of ion implantation, annealing, diffusion, physical vapor deposition (PVD), chemical vapor deposition (CVD), chemical mechanical polishing (CMP) and other technologies, and finally forms a dense microscopic integrated circuit structure on the wafer. In the manufacture of microscopic integrated circuits, different deposition technologies and processes are mainly used to deposit layers on the surface of the semiconductor wafer in steps, resulting in a very uneven surface of the wafer at the microscopic level. The manufacture of multi-layer microscopic circuits is formed layer by layer from bottom to top, so each layer of the processing technology requires the silicon wafer to be chemically mechanically polished (CMP) to make its surface flat enough to meet the needs of its upper layer processing.
[0003] Chemical mechanical polishing (CMP) is a very important process in the production of semiconductor chips. It is mainly responsible for removing excess materials and impurities on the surface and reducing surface defects such as roughness and scratches. The physical and mechanical properties of the polishing pad, such as wear resistance and adhesion, directly affect the processing quality and efficiency of semiconductor chips. CMP polishing generally includes two stages: rough polishing and fine polishing. For the fine polishing process, the polishing pad must be soft and have better followability on the non-flat silicon wafer surface. The polishing pad prepared by the condensation film forming method can meet the requirements of the polishing pad in the fine polishing process. That is, the resin solution is mixed with fillers, surfactants, etc., heated and stirred to obtain an intermediate, and then the intermediate is added to an organic solvent for dispersion to obtain a dispersion. Finally, the dispersion is mixed with the resin solution, stirred to obtain a slurry, and then the slurry is coated on the substrate and dried to obtain a polishing pad.
[0004] However, there are some problems with the existing polishing pad preparation methods. First, the resins used in the condensation film-forming method are mostly linear polymers with little or no chemical crosslinking, so their physical and mechanical properties are worse than those with crosslinked structures. Although the physical and mechanical properties can be improved by increasing the chemical crosslinking points, this can easily lead to the resin being insoluble in organic solvents, thereby affecting the preparation process of the polishing pad. Secondly, in order to make up for the above-mentioned deficiencies, the resin is usually reinforced by blending additives in the resin solution. However, these additives have fewer active functional groups or coarse particles, so the reinforcement effect is limited, and it is difficult to achieve the purpose of significantly improving the physical and mechanical strength of polyurethane. In addition, the physical and mechanical properties of the polishing pads prepared by the existing polishing pad preparation methods, such as wear resistance and adhesion, need to be improved to meet the needs of higher-precision semiconductor chip processing. Therefore, how to prepare a polishing pad with excellent physical and mechanical properties is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] In view of the problems existing in the prior art, a high-performance polishing material, a polishing pad and a preparation method and application thereof are provided.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a polishing material comprising a filler, a surfactant, an ether compound and a resin.
[0008] The polishing material of the present invention has good wear resistance and can be used for the polishing layer of a polishing pad. Preferably, the wear depth of the polishing layer does not exceed 70 μm, and the elongation at break is 390-500%.
[0009] In some embodiments, the filler is at least one of carbon black, carbon nanotubes, graphene and silica, preferably graphene and / or silica; further preferably silica; further preferably, the silica is fumed silica, the particle size of the fumed silica is 3-10 μm, the oil absorption value is 280-350 mL / 100 g, and the pH is 7.5-8.0.
[0010] In some embodiments, the surfactant is a surfactant containing an unsaturated double bond; preferably, the surfactant is at least one of a cationic surfactant, an anionic surfactant and a nonionic surfactant, and further preferably, the surfactant includes at least one of an amine salt type, a carboxylate type, a sulfonate type, a sulfate type, a phosphate type, a phosphate ester salt type, an amino acid type and a polyoxyethylene type. More preferably, the surfactant is at least one of a polymer of dimerization of dodecylbenzenesulfonic acid and linolenic acid salt, polyvinylpyrrolidone, isobutylene amide propyl trimethyl ammonium methyl sulfate and allyloxy hydroxypropane sulfonic acid sodium salt.
[0011] In some embodiments, the ether compound is an ether compound containing an unsaturated double bond, preferably ethylene glycol monoallyl ether and / or 4-hydroxybutyl vinyl ether.
[0012] In some embodiments, the resin is at least one of an amino resin, a polyurethane resin, a polyamide resin, an acrylate resin, a polysiloxane resin, a polyethylene resin, and a polypropylene resin.
[0013] In some embodiments, the mass ratio of the filler, the surfactant and the ether compound is 1-5:5-10:2-5; more preferably 2-4:7-9:3; and even more preferably 3:8:3.
[0014] In some embodiments, the resin accounts for 60-95% of the total mass of the filler, surfactant and ether compound; preferably 65-90%; more preferably 70-85%; and even more preferably 80%.
[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned polishing material, comprising the following steps:
[0016] S1, mixing fillers, surfactants and ether compounds, adding catalysts, heating and stirring to obtain an intermediate,
[0017] S2, adding the intermediate obtained in step S1 into an organic solvent and dispersing it to obtain a dispersion;
[0018] S3, adding the resin solution into the dispersion and stirring to obtain the polishing material.
[0019] In some embodiments, the catalyst in step S1 is at least one of azobisisobutyronitrile, dibenzoyl peroxide, diisopropylbenzene peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide and dimethyl azobisisobutyrate.
[0020] In some embodiments, the amount of the catalyst added in step S1 is 0.1-0.5% of the total mass of the surfactant and the ether compound; preferably 0.2-0.4%; and more preferably 0.25-0.35%.
[0021] In some embodiments, the heating and stirring in step S1 is: stirring at 70-95°C for 30-90 min, preferably stirring at 75-90°C for 40-80 min; more preferably stirring at 80-85°C for 60 min.
[0022] In some embodiments, the organic solvent in step S2 is at least one of N,N-dimethylformamide, N-methylpyrrolidone, acetone and chloroform.
[0023] In some embodiments, the amount of the organic solvent added in step S2 is 3-7 times the total mass of the surfactant and the ether compound; preferably 4-6 times; and more preferably 5-6 times.
[0024] In some embodiments, the dispersion in step S2 is ultrasonic dispersion. Preferably, the conditions of the ultrasonic dispersion are: temperature 40-70°C, 8-15kHz, ultrasound for 2-20min; more preferably: temperature 50-60°C, 10-12kHz, ultrasound for 5-10min.
[0025] In some embodiments, the mass percentage of the resin in the resin solution in step S3 is 20-50%, preferably 30-45%, and more preferably 35-40%.
[0026] In some embodiments, the stirring in step S3 is mechanical stirring, the stirring speed is 100-1000 r / min, and the stirring time is 10-30 min; preferably, the stirring speed is 300-800 r / min, and the stirring time is 15-20 min.
[0027] In a third aspect, the present invention further provides a polishing pad, at least one side of which comprises a polishing layer made of the above-mentioned polishing material.
[0028] In some embodiments, the polishing layer has a thickness of 60-200 μm, preferably 70-180 μm, and more preferably 80-150 μm.
[0029] In a fourth aspect, the present invention also provides a method for preparing the above-mentioned polishing pad, comprising the following steps: coating a polishing material on at least one side of a substrate, and drying to form a polishing layer.
[0030] In some embodiments, the coating comprises spraying and / or knife coating.
[0031] In some embodiments, the substrate is made of at least one of PET, PP and PE.
[0032] In some embodiments, the drying temperature is 40-60°C.
[0033] In a fifth aspect, the present invention also provides the use of the above-mentioned polishing material, the polishing material prepared by the above-mentioned preparation method, the above-mentioned polishing pad or the polishing pad prepared by the above-mentioned preparation method in the production of semiconductor chips.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention selects suitable fillers, surfactants and ether compounds, mixes them, adds a catalyst, heats and stirs, and obtains an intermediate. Among them, the unsaturated double bonds in the surfactants and ether compounds can undergo addition polymerization to form a special structure, and the filler is effectively embedded in the intermediate, avoiding sliding between the filler and the resin, improving the stability of the polishing material structure, and thus achieving excellent wear resistance.
[0036] 2. The present invention achieves effective reinforcement of the resin and greatly improves the physical and mechanical strength by optimizing the types and ratios of additives. By optimizing the preparation process, the wear resistance of the polishing pad is improved, meeting the needs of higher-precision semiconductor chip processing.
[0037] 3. The preparation method of the present invention is simple, easy to operate, and suitable for large-scale industrial production. Compared with the complicated process in the prior art that requires a large amount of fillers or high molecular weight resin materials, the preparation method of the present invention greatly simplifies the production process, improves production efficiency, and reduces production costs.
[0038] 4. The polishing material and polishing pad of the present invention have good versatility and can be widely used in the polishing process of various semiconductor chips. DETAILED DESCRIPTION
[0039] The present invention is described below through specific embodiments to make the technical solution of the present invention easier to understand and grasp, but the present invention is not limited thereto, and the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0040] The endpoints and any value of the scope disclosed in this article are not limited to the accurate scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Unless the context clearly indicates otherwise, the singular form "one", "a kind of" and "described" as used herein include singular and plural indicators. The numerical range described by the endpoint is included in all numerical values and fractions within the corresponding range, as well as the described endpoint.
[0041] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should belong to the scope of protection of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials can be obtained from commercial channels unless otherwise specified. The thickness of the PET substrate described in this embodiment is 180μm, the tensile strength at room temperature is 17.2MPa, and the elongation at break is 275%. The silica is fumed silica with a particle size of 5-8μm, an oil absorption value of 300-330mL / 100g, a pH of 7.7, and the solvent used in the resin solution is N,N-dimethylformamide.
[0042] Example 1 Preparation method of high performance polishing material
[0043] The steps include:
[0044] S1, take 30g of silicon dioxide, 80g of isobutylene amide propyl trimethyl ammonium methyl sulfate and 30g of ethylene glycol monoallyl ether, add 0.33g of azobisisobutyronitrile, heat to 80°C, stir for 40min, and obtain an intermediate.
[0045] S2, adding 550 g of N, N-dimethylformamide to the intermediate, and ultrasonically dispersing at a temperature of 55° C. and 10-12 kHz for 7 min to obtain a dispersion;
[0046] S3. Add 295 g of 38% by mass polyurethane resin solution into the dispersion and stir at 500 r / min for 18 min to obtain slurry.
[0047] Example 2 Preparation method of high performance polishing material
[0048] The steps include:
[0049] S1, take 10g of silicon dioxide, 50g of isobutylene amide propyl trimethyl ammonium methyl sulfate and 20g of ethylene glycol monoallyl ether, add 0.07g of azobisisobutyronitrile, heat to 70°C, stir for 90min, and obtain an intermediate.
[0050] S2, adding 210 g of N, N-dimethylformamide to the intermediate, and ultrasonicating at a temperature of 55° C. and 10-12 kHz for 7 min to obtain a dispersion;
[0051] S3, adding 240 g of 20% by mass polyurethane resin solution to the dispersion, stirring at 500 r / min for 20 min to obtain slurry;
[0052] Example 3 Preparation method of high performance polishing material
[0053] The steps include:
[0054] S1, take 50g of silicon dioxide, 100g of isobutylene amide propyl trimethyl ammonium methyl sulfate and 50g of ethylene glycol monoallyl ether, add 0.75g of azobisisobutyronitrile, heat to 95°C, stir for 30min, and obtain an intermediate;
[0055] S2, adding 1050 g of N, N-dimethylformamide to the intermediate, and ultrasonicating at a temperature of 55° C. and 10-12 kHz for 7 min to obtain a dispersion;
[0056] S3. Add 380 g of 50% by mass polyurethane resin solution into the dispersion and stir at 500 r / min for 20 min to obtain slurry.
[0057] Example 4 Preparation method of high performance polishing material
[0058] The difference between this embodiment and embodiment 1 is that the types of surfactant and ether compound are different (the amounts used remain unchanged).
[0059] Specifically, the polymer of dodecylbenzenesulfonic acid and linolenic acid dimer is used instead of methacrylamidopropyltrimethylammonium methylsulfate, and 4-hydroxybutyl vinyl ether is used instead of ethylene glycol monoallyl ether.
[0060] Example 5 Preparation method of high performance polishing material
[0061] The difference between this embodiment and embodiment 1 is that the types of surfactants are different (the dosage remains unchanged).
[0062] Specifically, allyloxyhydroxypropanesulfonic acid sodium salt is utilized in place of methacrylamidopropyltrimethylammonium methylsulfate.
[0063] Comparative Example 1 Preparation method of high performance polishing material
[0064] The difference between this comparative example and Example 1 is that the filler and the surfactant are different (the amount used remains unchanged).
[0065] Specifically, the particle size of the silicon dioxide is 5-8 μm, the oil absorption value is 400-450 mL / 100 g, and tallow dihydroxyethyl betaine is used instead of methacrylamidopropyl trimethyl ammonium methyl sulfate.
[0066] Comparative Example 2 Preparation method of high performance polishing material
[0067] The difference between this comparative example and Example 1 is that the mass ratios of the filler, the surfactant and the ether compound are different.
[0068] Specifically, the steps include:
[0069] S1, take 30g of silicon dioxide, 30g of isobutylene amide propyl trimethyl ammonium methyl sulfate and 80g of ethylene glycol monoallyl ether, add 0.33g of azobisisobutyronitrile, heat to 80°C, stir for 40min, and obtain an intermediate.
[0070] S2, adding 550 g of N, N-dimethylformamide to the intermediate, and ultrasonically dispersing at a temperature of 55° C. and 10-12 kHz for 7 min to obtain a dispersion;
[0071] S3. Add 295 g of 38% by mass polyurethane resin solution into the dispersion and stir at 500 r / min for 18 min to obtain slurry.
[0072] Comparative Example 3 Preparation method of high performance polishing material
[0073] The difference between this comparative example and Example 1 is that there is no intermediate preparation process.
[0074] The steps include:
[0075] S1, add 60g of silicon dioxide to 550g of N,N-dimethylformamide, and disperse ultrasonically at 55°C and 10-12kHz for 7min to obtain a dispersion;
[0076] S2. Add 295 g of 38% by mass polyurethane resin solution into the dispersion and stir at 500 r / min for 18 min to obtain slurry.
[0077] 1. Wear resistance test of polishing materials
[0078] The test was carried out according to QB / T2726 2005 leather physical and mechanical test wear resistance determination method.
[0079] The test conditions are:
[0080] Tungsten-carbon wheels, maximum diameter 51.7mm, minimum diameter 44.0mm;
[0081] Grinding wheel weight 500g;
[0082] Rotation speed: 65r / min;
[0083] Number of revolutions:2500.
[0084] Preparation of polishing pad: The slurry was coated on the upper surface of a PET substrate having a thickness of 180 μm, and dried at 40-60° C. to obtain a polishing pad having a polishing layer. The wear resistance of the polishing pad samples prepared in the examples and comparative examples was tested, and the test was repeated 6 times, and the wear depth was recorded. The results are shown in Table 1 below. The greater the wear depth, the worse the wear resistance of the polishing pad.
[0085] Table 1
[0086] Polishing layer thickness μm Wear depth μm Example 1 147 57.4±3.5a Example 2 138 68.1±3.8a Example 3 145 64.8±4.2a Example 4 143 50.7±3.2a Example 5 150 53.6±4.0a Comparative Example 1 146 102.5±8.9b Comparative Example 2 149 107.9±9.5b Comparative Example 3 150 110.0±7.6b
[0087] Note: Different letters in the table indicate significant differences among the groups (P < 0.05).
[0088] According to the results, the wear depth of the polishing materials prepared in Examples 1-5 of the present invention is about 50-68 μm, and there is no significant difference among the groups (P>0.05), indicating that the polishing materials prepared in the present invention have good wear resistance.
[0089] At the same time, according to the experiments of Comparative Example 1 and Example 1, the wear depth of the polishing pad prepared by Comparative Example 1 using silica with an oil absorption value of 400-450mL / 100g and tallow dihydroxyethyl betaine as filler and surfactant respectively reached 102.5μm, and the wear resistance was poor. Compared with the polishing material prepared in Example 1, the wear depth had a significant difference (P<0.05). It shows that the wear resistance of the polishing material prepared in Example 1 is significantly better than that of Comparative Example 1. It can be seen that in the technical solution claimed by the present invention, silica and surfactant have a greater influence on the wear resistance of the polishing material.
[0090] According to the single factor experiment of Comparative Example 2 and Example 1, the wear depth of the polishing pad prepared by Comparative Example 2 is 107.9 μm, and the wear resistance is poor. Compared with the polishing material prepared in Example 1, the wear depth has a significant difference (P < 0.05). It shows that the wear resistance of the polishing material prepared in Example 1 is significantly better than that of Comparative Example 2. It can be seen that the amount of filler, surfactant and ether compound used in the technical solution claimed by the present invention has a greater influence on the wear resistance of the polishing material.
[0091] According to Comparative Examples 1-3, the wear depth of the polishing materials prepared in Comparative Examples 1-3 reached 132.5-110.0 μm, and there was no significant difference between the groups (P>0.05), indicating that the wear resistance of the polishing materials prepared in Comparative Examples 1-3 of the present invention is poor. By comparing Comparative Examples 2 and 3, it can be seen that there is no significant difference in the wear depth of the polishing materials prepared by the two (P>0.05), indicating that in the technical scheme claimed for protection by the present invention, the amount of conventional fillers, surfactants and ether compounds has no effect on the wear resistance of the polishing material.
[0092] 2. Tensile strength and elongation at break of polishing materials
[0093] The test was conducted in accordance with ASTM D412, a standard for the tensile properties of vulcanized rubber and thermoplastic elastomers, at a tensile speed of 50 mm / min.
[0094] The results are shown in Table 2. The greater the tensile strength, the better the mechanical properties of the polishing pad; the greater the elongation at break, the better the mechanical properties of the polishing pad.
[0095] Table 2
[0096] Tensile strength MPa Elongation at break % Example 1 21.8 420 Example 2 20.4 405 Example 3 21.2 390 Example 4 22.9 465 Example 5 23.7 500 Comparative Example 1 18.7 385 Comparative Example 2 18.3 380 Comparative Example 3 17.5 375
[0097] According to the results, the polishing pads prepared in Examples 1-5 of the present invention have a tensile strength greater than 20 MPa and an elongation at break of 390-500%, indicating that the polishing pads of the present invention have good mechanical properties.
[0098] At the same time, by comparing the experiments of Comparative Examples 1-3 and Example 1, it can be seen that in the technical scheme claimed to be protected by the present invention, the types of fillers and surfactants and the amounts of fillers, surfactants and ether compounds have a great influence on the mechanical properties of the prepared polishing pad.
[0099] In summary, the intermediate of the present invention has a great influence on the wear resistance and mechanical properties of the prepared polishing material, which may be related to the special structure formed by the addition polymerization reaction of the unsaturated double bonds in the surfactant and the ether compound.
[0100] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A polishing material for a polishing layer of a polishing pad, characterized in that: The polishing material includes filler, surfactant, ether compound and resin; The wear depth of the polishing layer does not exceed 70 μm, and the elongation at break is 390-500%.
2. The polishing material according to claim 1, characterized in that: The filler is at least one of carbon black, carbon nanotubes, graphene and silicon dioxide; the surfactant is a surfactant containing unsaturated double bonds; and the ether compound is an ether compound containing unsaturated double bonds.
3. The polishing material according to claim 1, characterized in that The mass ratio of the filler, surfactant and ether compound is 1-5:5-10:2-5; The resin accounts for 60-95% of the total mass of the filler, surfactant and ether compound.
4. The polishing material according to claim 2, characterized in that: The filler is silicon dioxide; the surfactant is at least one of a cationic surfactant, an anionic surfactant and a non-ionic surfactant; the ether compound is ethylene glycol monoallyl ether and / or 4-hydroxybutyl vinyl ether; and the resin is at least one of an amino resin, a polyurethane resin, a polyamide resin, an acrylate resin, a polysiloxane resin, a polyethylene resin and a polypropylene resin.
5. The method for preparing the polishing material according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing fillers, surfactants and ether compounds, adding catalysts, heating and stirring to obtain an intermediate, S2, adding the intermediate obtained in step S1 into an organic solvent and dispersing it to obtain a dispersion; S3, adding the resin solution into the dispersion and stirring to obtain the polishing material.
6. The preparation method according to claim 5, characterized in that: The catalyst in step S1 is at least one of azobisisobutyronitrile, dibenzoyl peroxide, diisopropylbenzene peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide and dimethyl azobisisobutyrate; The amount of the catalyst added is 0.1-0.5% of the total mass of the surfactant and the ether compound; The organic solvent in step S2 is at least one of N,N-dimethylformamide, N-methylpyrrolidone, acetone and chloroform; The amount of the organic solvent added in step S2 is 3-7 times the total mass of the surfactant and the ether compound; The mass percentage of the resin in the resin solution in step S3 is 20-50%.
7. A polishing pad, characterized in that: At least one side of the polishing pad contains a polishing layer made of the polishing material according to any one of claims 1 to 4 or the polishing material obtained by the preparation method according to any one of claims 5 to 6.
8. The method for preparing the polishing pad according to claim 7, comprising the steps of: coating the polishing material on at least one side of the substrate, and drying to form a polishing layer.
9. The preparation method according to claim 8, characterized in that: The material of the substrate is at least one of PET, PP and PE; The drying temperature is 40-60°C.
10. Use of the polishing material according to any one of claims 1 to 4, the polishing material prepared by the preparation method according to any one of claims 5 to 6, the polishing pad according to claim 7 or the polishing pad prepared by the preparation method according to any one of claims 8 to 9 in the production of semiconductor chips.
Citation Information
Patent Citations
Polishing pad
CN102712074A
Chemical mechanical polishing pad capable of improving polishing efficiency and preparation method of chemical mechanical polishing pad
CN114670119A
Chemical mechanical polishing pad and preparation thereof
CN115958527A
High-wear-resistance chemical mechanical polishing pad as well as preparation method and application thereof
CN115972084A
Yellowing-resistant polyurethane for polishing pad and preparation process of yellowing-resistant polyurethane
CN118027341A